Adolescent stress: A predictor of dieting behaviors in youth with overweight/obesity. (1st April 2020) - Ajibewa, Tiwaloluwa A.; Zhou, Megan; Barry, Mikayla R.; Miller, Alison L.; Sonneville, Kendrin R.; Leung, Cindy W.; Hasson, Rebecca E.
Abstract: Objective: To examine associations between psychological stress and dieting behavior along with the heterogeneity of this association by gender and race in a diverse sample of adolescents with overweight/obesity. Methods: One hundred and sixty-one adolescents between the ages of 13–19 years of age with overweight/obesity (65% female; 53% non-Hispanic black/47% non-Hispanic white; age: 16.7 ± 1.7 years) were recruited from Southeast MI and included in this analysis. Psychological stress was measured using the Perceived Stress Scale, and dieting behavior was assessed using the dieting subscale from the Eating Attitudes Test (EAT-26) questionnaire. Multivariable linear regression models were conducted to examine the association between psychological stress and dieting behavior by gender and race. Results: Psychological stress was significantly associated with dieting (β = 0.18 ± 0.06; p < 0.01), with greater stress associated with greater frequency of dieting behavior. This relationship remained significant (β = 0.15 ± 0.06; p = 0.016), even when controlling for covariates (age, body fat, gender, race, and pubertal development). There were no statistically significant differences in the association of psychological stress and disordered eating indices by gender or race/ethnicity (p's > 0.05). Conclusions: Increased psychological stress is associated with increased dieting behavior among adolescents with overweight/obesity. These findings suggest that psychological stress equally affects dieting behavior among adolescents with overweight/obesity, regardless of gender and race. Future studies should seek to identify the unique sources of psychological stress that contribute to increased dieting behavior among adolescents with overweight/obesity.